Lógicas de interacción en interfaces gráficas de banca online (AMBA, 2021-2022) - Ravitti, Florencia (2023)
The passage from media societies to mediatized societies gave rise to a hypermedia system that modified people's relationship with a variety of institutions (Scolari, 2008; Verón, 2013; Carlón, 2020). Among them is the banking institution, whose online banking interface, or homebanking, is the object of this study.\nThis research focuses on the analysis of online banking interfaces in both their production and reception/recognition: on the one hand, the interaction contract proposed by two homebanking platforms (BBVA from the private sector, and Banco Provincia as a state bank), and on the other hand, the study of responses in interviews with users and the observation of the activated logics upon interacting with these interfaces.\nTo this end, this research's methodological design is based on an empirical study of interfaces as discourse and its reception, analyzed through the lens of a theoretical framework consisting of Verón's theory of social discourses (1998, 2013), Scolari's concept of interaction contract (2004, 2018), Verón's reading contract (1985), and with contributions from user experience design (Norman, 2013; Garrett, 2011).